Mechanical and microstructural properties of cement-stabilized soft clay improved by sand replacement and biochar additive for subgrade applications - Kittipong Kunchariyakun; Patimapon Sukmak; Gampanart Sukmak; Veena Phunpeng; Suksun Horpibulsuk; Arul Arulrajah; Annan Zhou (Developments in the Built Environment)
Biochar (BC) is an eco-friendly material produced through coal pyrolysis and can improve the mechanical properties of cement-based construction and building materials. This research study explored the effects of BC and natural sand (Sand) replacement on the improved static and cyclic response of blended hydraulic cement (BHC) stabilized soft clay (SC) as a greener subgrade material. Unconfined compressive strength (UCS), indirect tensile stress (ITS), and indirect tensile fatigue life (ITFL) of the BHC-stabilized SC-BC-Sand samples were examined. Adding 10% BC to the BHC-stabilized samples was found to enhance cementitious products due to its porous structure and high water absorbability. The UCS, ITS and ITFL at this optimum ingredient were improved up to 315%, 347% and 862%, respectively, compared to the BHC-stabilized SC. Fourier transform infrared spectrometer, thermogravimetry differential thermal analysis and a scanning electron microscope with energy-dispersive -ray spectroscopy analyses the BHC-stabilized sample at the optimum ingredient showed the highest C-S-H and Ca(OH)2 in the pores. This investigation will encourage the utilization of BC to create both environmentally friendly and durable stabilized subgrade material.